Comprehensively-upgraded polymer electrolytes by multifunctional aramid nanofibers for stable all-solid-state Li-ion batteries. (March 2020) - Liu, Lehao; Lyu, Jing; Mo, Jinshan; Yan, Hejin; Xu, Lele; Peng, Peng; Li, Jingru; Jiang, Bing; Chu, Lihua; Li, Meicheng
Abstract: Satisfactory ionic conductivity and mechanical stability are the prerequisites for the applications of solid polymer electrolytes in Li-ion batteries. Herein, by using aramid nanofibers (ANFs) as multifunctional nano-additives, comprehensively-upgraded polyethylene oxide (PEO)-LiTFSI electrolytes with 3D ANF network frames are achieved through the hydrogen-bond interactions between the 1D ANFs. The hydrogen-bond interactions between the ANFs and the PEO chains and TFSI ‒ anions can greatly prevent the ANF agglomeration, suppress the PEO crystallization, facilitate the LiTFSI dissociation, and prolong the ion transport paths at the 3D ANF framework/PEO-LiTFSI interfaces. Thus, the ANF-modified electrolytes show superior room-temperature conductivity of 8.8 × 10 −5 S cm −1 . The ANF-containing composite electrolytes also display greatly-enhanced mechanical strength, thermostability, electrochemical stability and interfacial resistance against Li dendrites, attributed to the 3D ANF framework. In consequence, the composite electrolyte-based LiFePO4 /Li cells exhibit better rate performance and cycling stability (e.g., 135 mAh g −1 after 100 cycles at 0.4 C). This work offers a novel and effective strategy to comprehensively upgrade polymer electrolytes by employing organic nanofillers in the composite electrolyte design and revealing the ion transport mechanism for promising all-solid-state Li-ion battery applications. Graphical abstract: Image 1 Highlights: Multifunctional aramid nanofibers are utilized to improve the overall properties of polymer electrolytes. Nanofiber-based electrolytes show higher ion conductivity and mechanical/electrochemical stabilities. Interfacial resistance against Li dendrites is greatly enhanced by the multifunctional nanofillers. Composite electrolyte-based all-solid-state Li-ion batteries exhibit superior cycling performance.